The Algorithmic Compassion: How AI is Reshaping the Future of End-of-Life Care - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The Algorithmic Compassion: How AI is Reshaping the Future of End-of-Life Care The integration of Artificial Intelligence (AI) into healthcare is rapidl...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Medical Ethics; Precision Medicine